2006
DOI: 10.1007/s00595-005-3139-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated Bedside Measurement of Penile Blood Flow Using Pulse-Volume Plethysmography

Abstract: The form PWV/ABI is a useful tool for assessing pelvic hemodynamics and diagnosing vasculogenic impotence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…As shown in Table I , the general plethysmograph types are: water [4-8], air, strain gauge, impedance, and photoelectric.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table I , the general plethysmograph types are: water [4-8], air, strain gauge, impedance, and photoelectric.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the PBI, which was first proposed in 1971, 10,34 has been reported to have a high rate of error in distinguishing vasculogenic from non-vasculogenic ED. 16 On the other hand, although the Rigiscan is regarded as a reliable tool in assessment of erectile function since 1985, 4,9,24 it requires an erectile penis the rigidity of which may vary with the degree of stimulation and also with the psychological status.…”
Section: Discussionmentioning
confidence: 99%
“…PBI was calculated by dividing systolic blood pressure (SBP) of left arm with that of the penis. 10,34 After deflation of the penile cuff and reconnecting the rubber tubing to the PAWA system, a cuff pressure of 80 mmHg was applied to the penis for 4 min during which the arterial waveform signals were acquired, which served as the baseline (Fig. 4).…”
Section: Pawa For Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that the PBI values obtained by the device signifi cantly correlated with the data obtained by Doppler ultrasound measurement. 6 The PBI could be repeatedly measured with this device without manual manipulation during surgery.…”
Section: Monitoring Of Penile Blood Flowmentioning
confidence: 99%